A comparative study on online advice-seeking strategies between Malaysian and Australian women - Pung, Wun Chiew; Ho, Ai Ping (Penerbit Universiti Kebangsaan Malaysia, 2022)
Advice discourse is common in our everyday life. As such, research on advice is diverse and covers advice-related communicative practices such as advice-seeking, advice-giving and reception to advice. Past research on advice has also examined various factors affecting advicerelated practices such as the relationship between advice and politeness, gender, and characteristics of interlocutors. Although advice is a much-researched area, comparative studies that attempt to compare advice-seeking strategies in two similar contexts are scarce. The present study seeks to fulfill this gap, hence a comparative study that compares the strategies used by women in Malaysia and Australia when they seek advice on infertility treatment in a Malaysian online forum and in an Australian online forum is carried out. A total of 100 advice-seeking messages from each forum are examined using Locher’s (2006) content analysis method that involves analysis of the discursive moves, relational work, and linguistic realisations of moves in the advice-seeking messages. The results show that although there is homogeneity in many aspects in both forums, there are still variations in the women’s adviceseeking strategies due to cultural backgrounds, specifically on the frequency and levels of problem disclosure, as well as the use of local slangs and syntax constructions that are typical of their cultural community. The study provides insights about how cultural elements shape one’s advice-seeking strategies, subsequently contributing to our understanding of crosscultural pragmatics.